The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10584-009-9682-3
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the dilemmas of climate policy in Europe: evidence from policy evaluation studies

Abstract: Climate change is widely recognised as a 'wicked' policy problem. Agreeing and implementing governance responses is proving extremely difficult. Policy makers in many jurisdictions now emphasise their ambition to govern using the best available evidence. One obvious source of such evidence is the evaluations of the performance of existing policies. But to what extent do these evaluations provide insights into the difficult dilemmas that governors typically encounter? We address this question by reviewing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…What 'short-cuts' and rationales do they use to overcome complex problems? We identify three dilemmas that are addressed in the literature (Adger et al, 2009;Haug et al, 2010;Walker et al, 2011;Mees et al, 2012;Preston et al, 2013): value uncertainty, planning horizon problems, and indirect benefits. Figure 1 illustrates our conceptual framework based on three spheres: (1) climate adaptation as a planning issue; (2) uncertainty and complexity as a decision problem; and (3) the decisions problems are bundled into thematic clusters of the institutional dilemmas.…”
Section: Institutional Dilemmas: Clustering Uncertainty and Reducing mentioning
confidence: 99%
“…What 'short-cuts' and rationales do they use to overcome complex problems? We identify three dilemmas that are addressed in the literature (Adger et al, 2009;Haug et al, 2010;Walker et al, 2011;Mees et al, 2012;Preston et al, 2013): value uncertainty, planning horizon problems, and indirect benefits. Figure 1 illustrates our conceptual framework based on three spheres: (1) climate adaptation as a planning issue; (2) uncertainty and complexity as a decision problem; and (3) the decisions problems are bundled into thematic clusters of the institutional dilemmas.…”
Section: Institutional Dilemmas: Clustering Uncertainty and Reducing mentioning
confidence: 99%
“…An example of a reframing-based CPI is the inclusion of annual energy tax increases as climate policy, when these are already instituted for fiscal reasons. As observed by Haug et al (2010), several longstanding measures reported as climate policies were initially designed as responses to other problems. At a strategic level, a level above that of policy instruments, support for many energy technologies has been reframed as climate policy without significant change at the level of policy instruments (Lovell et al 2009, Kivimaa andMickwitz 2011).…”
Section: Defining Cpimentioning
confidence: 99%
“…Finally, many single EU environmental objectives have been criticized. For instance, Spangenberg (2010) and Steurer & Berger (2011) critiqued sustainable development; McLauchlan & João (2012) and Sheate (2012) critiqued the safe environment objective; and Haug et al (2010), Capros et al (2011), and Brouwer et al (2013) critiqued greenhouse gas (GHG) reduction. In contrast, few studies have scrutinized the overall EU environmental policy system in terms of its coherence (i.e., consistency of policies within a framework), efficiency (i.e., ability of policies to meet their objectives), and independence (i.e., logical priority of objectives over policies).…”
Section: Introductionmentioning
confidence: 99%